Epidemiological and anatomopathological profile of colorectal cancer: A cross-sectional study - Lahoucine Amsdar; Jamal Tikouk; Mohamed Amine Baba; Hafid Arzoug; Jaouad Elkhalladi; Salima Zerouali; Kenza Oqbani; Ghizlane Rais; Mehdi Soufi (Journal of Public Health in Africa)
Background: Colorectal cancer (CRC) remains one of the leading causes of cancer-related deaths globally, with incidence and mortality rates exhibiting geographical disparities.